Evaluation of health promotion training for the Western Australian Aboriginal maternal and child health sector - Wilkins, Alexa; Lobo, Roanna; Griffin, D.; Woods, H. (Australian Health Promotion Association, 2015)
Issue addressed: The evaluation of health promotion training for the Western Australian (WA) Aboriginal maternal and child health (MCH) sector. Methods: Fifty-one MCH professionals from five regions in WA who attended one of three health promotion short courses in 2012–2013 were invited to complete an online survey or a telephone interview, between 4 to 17 months post-course. Respondents were asked how they had utilised the information and resources from the training and to identify the enabling factors or barriers to integrating health promotion into their work practices subsequently. Results: Overall response rate was 33% (n = 17); 94% of respondents reported they had utilised the information and resources from the course and 76% had undertaken health promotion activities since attending the course. Building contacts with other MCH providers and access to planning tools were identified as valuable components of the course. Barriers to translating knowledge into practice included financial constraints and lack of organisational support for health promotion activity. Conclusions: Health promotion training provides participants with the skills and confidence to deliver health promotion strategies in their communities. The training presents an opportunity to build health professionals’ capacity to address some determinants of poor health outcomes among pregnant Aboriginal women and their babies. So what?: Training would be enhanced if accompanied by ongoing support for participants to integrate health promotion into their work practice, organisational development including health promotion training for senior management, establishing stronger referral pathways among partner organisations to support continuity of care and embedding training into MCH workforce curricula.